Data for the paper "Process and economic evaluation of an on-board capture system for LNG-fueled CO2 carriers" - Awoyomi, Adeola; Patchigolla, Kumar; Anthony, Ben (Cranfield University, 2019)
Table showing the results obtained from the economic analysis of the capture integration. All graphs can be generated from the given streams.
Keywords: 'On-board capture'; 'maritme carbon capture'; 'zero-emission ships'; 'post-combustion capture'; 'marine engine propulsion'; 'Power and Energy Systems Engineering (excl. Renewable Power)'; 'Energy Generation; Conversion and Storage Engineering'; 'Carbon Capture Engineering (excl. Sequestration)'; 'Carbon Sequestration Science'